Diabetic status of patients with leprosy in Kuwait - Mohammad A. Saraya; Mariam A. Al-Fadhli; Jafar A. Qasem (Elsevier, 2012)
Summary: Objective: The aim of this study was to screen for diabetes mellitus in leprosy patients to elucidate whether leprosy infection may play a role in the pathogenesis of diabetes mellitus in this population. Subjects and methods: Thirty patients of different ages and of both sexes with various types of leprosy were included in this study. In addition, 15 healthy individuals of comparable age and sex who had no family history of diabetes mellitus were identified as controls. In both groups, determinations of fasting and postprandial blood sugar, an oral glucose tolerance test (OGTT), measures of fasting serum insulin and pro-inflammatory cytokine tumor necrosis factor alpha (TNFα), as well as calculations using the Homeostasis Model Assessment for Insulin Resistance (HOMA-IR), were carried out. Result: Approximately 13.3% of the leprosy patients were diabetic, and 37.7% were in pre-diabetic. The highest incidences of diabetes and pre-diabetes were in lepromatous leprosy (10% and 20%, respectively); a lower incidence of pre-diabetes (6.6%) was observed in tuberculoid leprosy; and the lowest incidence of diabetes (0.0%) was noted in borderline leprosy patients. Although normal healthy persons were not diabetic (0%), 20% were pre-diabetic. Conclusion: This study revealed that the incidence of diabetes was higher in the leprosy patients than in the control group. As a result, we recommend that all leprosy patients should be screened for diabetes. Keywords: Leprosy, Diabetes, Insulin resistance, Tumor necrosis factor alpha, Kuwait